Identification of tropomyosin and arginine kinase as major allergens of Portunus pelagicus (blue swimming crab) - M Rosmilah, M Shahnaz, H.M.Y Zailatul, A Noormalin, I Normilah, (N/A, 2012)
Identification of tropomyosin and arginine kinase as major allergens of Portunus pelagicus (blue swimming crab) by M Rosmilah, M Shahnaz, H.M.Y Zailatul, A Noormalin, I Normilah,